İSLAM HUKUKUNDA EŞİTLİĞİ BOZAN FAKTÖRLER - MEYDANOĞLU, AYŞE (Fırat Üniveristesi, 2011)
Esitlik kavramına farklı bir bakıs açısıyla yaklasan slam hukuku, bu kavramınaltını kendine özgü ifadelerle doldurmustur. Esitlikten ziyade adalet prensibi üzerindeduran bu yaklasım, temel haklarda bütün insanları esit görürken, farklı yetenek vekabiliyetlerden kaynaklanan farklılasmayı da göz ardı etmemistir. Bu baglamda temelgaye hak edene hakkını teslimdir.Bazen bu hakkın tesliminde esitligi bozan unsurlar ortaya çıkmaktadır. Bunlar,cinsiyet, akıl, bilgi, sıhhat veya din ayrılıgı gibi faktörlerden kaynaklanabilir. Ortayaçıkan bu engellerde esitligi bozmak bir esitsizlik olabilir. Ancak her esitsizlikadaletsizlik degildir.Anahtar kelimeler: Esitlik, hak, adalet, ehliyet, slam hukuku, esitsizlik.

The Islamic Law that approaches to the term of equality with a differentviewpoint has filled the base of this term with distinctive definitions. This approach thatemphasizes more on the principle of justice than equality, in fundamental rights, has notignored the differentiation originated from different abilities and capabilities. In thissense, the basic goal is to give the deserver what he/she has deserved.Sometimes, in the delivery of this right, there appear some factors disrupting theequality. They may be arisen from sex, wisdom, health or separation of religion. It maybe an inequality to disrupt the equality for these generated drawbacks.Key Words: Equality, right, justice, competency, Islamic Law, inequality.
The factors disrupting the equality in Islamic Law
Keywords: Hukuk; Din